2022
DOI: 10.1007/s12144-022-03277-7
|View full text |Cite
|
Sign up to set email alerts
|

Facial impression of trustworthiness biases statement credibility unless suppressed by facemask

Abstract: The impression of trustworthiness based on someone’s facial appearance biases our subsequent behavior toward that subject in a variety of contexts. In this study, we investigated whether facial trustworthiness also biases the credibility of utterances associated with that face (H1). We explored whether this bias is mitigated by utterances eliciting reasoning, i.e. explanations (as opposed to factual statements; H2). Moreover, we hypothesized that overimposing facemasks on those faces could enhance/reduce utter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Subsequently, to minimize the individual differences in the reading times RTs possibly due to the different devices employed by the participants (and the difference between fast-readers and slow-readers), the RTs were parameterized in a subtractive fashion (Marini et al 2022 ), namely by subtracting, for each trial, the whole task average RT of that participant to the RT of the single trial, as follows: …”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, to minimize the individual differences in the reading times RTs possibly due to the different devices employed by the participants (and the difference between fast-readers and slow-readers), the RTs were parameterized in a subtractive fashion (Marini et al 2022 ), namely by subtracting, for each trial, the whole task average RT of that participant to the RT of the single trial, as follows: …”
Section: Resultsmentioning
confidence: 99%
“…The greatest difference concerning the negative influence of face masks was found within individual therapy on both ends, professionals and patients especially for the aspects of “being understood by the therapist,” “my therapist means it honestly,” and “being able to trust the patient.” Although there are mixed findings on the assessment of the trustworthiness of a counterpart wearing a face mask, an overall tendency toward a negative bias in the assessment of trustworthiness can be derived from current literature (e.g., Carbon, 2020 ; Gabrieli and Esposito, 2021 ; Marini et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, face masks could create unfamiliar distance and impair the feeling of coherence (e.g., Wong et al, 2013 ). As recent research in the context of the COVID-19 pandemic has shown, there is also a striking influence on the trustworthiness of the interaction partner through the wearing of a mask ( Biermann et al, 2021 ; Malik et al, 2021 ; Cannito et al, 2022 ; Marini et al, 2022 ). As proposed in the concept of epistemic trust ( Fonagy and Allison, 2014 ), basal trust in a reference person as a secure source of information can be perceived as core element of a functioning, resilient therapeutic relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that these judgements are related to behaviours during the pandemic. Nevertheless, further studies are required that investigate whether the effects of masks on implicit social judgments and behaviours differ between individuals with BPD and HC (see for studies in HC e.g., [54][55][56]). Finally, the study was implemented as an online-survey due to the restrictions imposed by the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%